PENGARUH PUPUK P DAN K TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG HIJAU Vigna Radiata L PADA MEDIA TANAH PASIR PANTAI(THE EEFECTS OF P AND K FERTILIZERS TO THE DEVELOPMENT AND YIELDS OF GREEN BEAN PLANTS Vigna Radiata L IN THE BEACH SAND SOIL MEDIA) - Widarawati, Rosi; Harjoso, Tri (Pembangunan Pedesaan, 2011)
The purposes of this study were to see the effect of P fertilizer on the growth and yield of green beans in the highest dose, the effect of K fertilizer on growth and yield of green beans in the highest dose, the interaction effect of fertilizer P and K on growth and yield of green beans in the best treatment combination. The experiment was conducted in the plastic house experiment station Faculty of Agriculture, Unsoed from February 2010-April 2010. The design was Randomized Block Design with three replications. Factors tested the P fertilizer consisted of four levels: without P fertilizer (P0), P fertilization at 45 kg P2O5/ha (P1), P fertilization at a dose of 90 kg P2O5/ha (P2), P fertilization at a dose of 135 P2O5/ha kg (P3). K fertilizer consisted of four levels: without fertilizer K (K0), K fertilization at a dose of 50 kg K2O/ha (K1), K fertilization at a dose of 75 kg K2O/ha (K2), K fertilization with 100 kg K2O (K3 ). The combination of the two factors was 16. The observed variables were plant height, leaf number trifoliat, leaf area, canopy dry weight, root dry weight, total root length, number of pods per plant, seed number per pod, 100 seed weight, seed weight per plant and harvest index. The results showed that P fertilizer affected on plant height, leaf area, canopy dry weight, root dry weight, and weight of seeds per plant. Fertilizer K did not affect all variables. Interactions between fertilizer P and K to produce 135 kg of fertilizer P P2O5/ha to provided the highest root dry weight (7.79 g) when given fertilizer K 50 kg K2O. Provision of 90 kg fertilizer P P2O5/ha to provided the highest number of pods per plant (12.57 pieces) when given 50 kg K2O K fertilizer. Provision of 90 kg fertilizer P P2O5/ha to provided the highest seed weight per plant (7.66 g) when given 50 kg K2O K fertilizer.